Measurement of Successful Implementation of Institution Level Financial Application System (SAKTI) Web Full Module with DeLone and McLean Model in in the Directorate General of Military Courts and State Administrative Courts - Sofiyatul Muminah; Dika Putri Metalica (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The Ministry of Finance has developed an Agency Level Financial Application System (SAKTI) which is mandatory to be used by all work units of Ministries/Institutions managing funds sourced from the APBN. SAKTI's main features include database integration, single entry pint, applying accrual-based accounting and data security guarantees. SAKTI was built to support the principles of orderly, effective, efficient, economical, transparent, accountable, integrated and performance-based financial management. The purpose of this study was to measure how successful the implementation of the full web SAKTI in the Directorate General of Military Courts and State Administrative Courts was using the Delon and McLean model. Data was collected through survey method and then analyzed using Partial Least Square (PLS). The results showed that of the 4 hypotheses that were stated to be accepted and the other 2 were rejected.